Pengembangan UMKM (Inovasi Pembuatan Kerupuk Pisang Bersama Masyarakat Desa Tanjung Sialang sebagai Peluang Usaha dalam Meningkatkan Ekonomi Masyarakat) - Nur Hayati; Riski Afwina Seruni Dewi; Khadijah; Rodiyah; Riyadotul Jannah; Nur Halimah; Ali Zul Fikri; Candra Husein; Rayhan Jhonson; Hamdanil (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Tanjung Sialang Village is located in Siabu District, Mandailing Natal Regency, and is known for its agricultural potential, especially bananas. However, bananas have generally been sold only as fresh fruit at low prices, so the community has not yet benefited from added value. To address this issue, a business development initiative was carried out through the innovation of banana cracker production as an effort to improve the local economy. The aim of this activity is to create new business opportunities based on local resources while encouraging the community’s independence in developing small-scale enterprises. The methods applied included socialization, training, production mentoring, and marketing practices. The results show that the community succeeded in producing good-quality banana crackers, packaging the products more attractively, and learning simple marketing strategies. In addition, this initiative increased entrepreneurial motivation and opened new economic opportunities that can support family welfare. In conclusion, banana cracker innovation has proven to be a sustainable local-based business alternative that positively contributes to the economic growth of Tanjung Sialang Village.